An Integrative Approach for Sustainable Management of Construction and Demolition Waste in Antipolo City, Philippines - Qusiquisan, Maria Bernadeth B. (Indonesian Journal of Community Services, 2024)
Infrastructure projects have always been a significant opportunity for the government to foster social and economic development. However, infrastructure project results accumulate substantial waste. Defined operationally as construction and demolition waste (CDW), they account for 30% of waste sent to landfills. Focusing on the urban areas in Antipolo City as a specific case, this study provides an integrated framework for sustainable CDW management. Corroborating data results from the Delphi method, this framework comprises three approaches including the development of specific regulations on CDW management, implementing the circular economy waste management strategies in every stage of the project life cycle, and improving the current waste collection and disposal system in the city. Results also showed that 53% of construction stakeholders entrust private haulers with CDW collection and disposal. This system poses the question of who shall be responsible for managing the waste produced from the project. Recommendations are therefore provided that will serve as a foundation to establish a policy addressing the issues and concerns of CDW management.